Facelift: Shining Up a Silver Shrine (The Biblical archaeology review, 2020)
In 990, the Leon Levy Expedition to Ashkelon uncovered a small shrine within a house on the ramparts of Tel Ashkelon, located on Israel’s Mediterranean coast. Inside a ceramic vessel rested a small calf figurine. Made of bronze and gilded with silver, the calf had a detached leg but was missing only its left […]